Modelling of SST/BES and its application to power quality improvement. (1st January 2011) - Zeng, Jie; Zhang, Buhan; Mao, Chengxiong; Li, Yan; Fan, Shu
A solid state transformer incorporated with battery energy storage (SST/BES) is proposed in this paper. The SST has the capability of power-factor correction and controls bi-directional energy flow, but it cannot protect loads from input-voltage momentary interruptions because SST has no energy storage in the DC link. The proposed system, which consists of an SST, a battery bank and a bi-directional DC-DC converter, can be used to improve the reliability of residential power supply. With the help of BES, which is connected to the low voltage DC link in SST via the DC-DC converter, the SST/BES can supply the power demanded by the residential load in the event of the voltage sags and momentary interruptions of the input voltage. Necessary models are developed and control strategies are presented in a detailed manner. Time domain simulations are carried out by using MATLAB/Simulink to demonstrate the effectiveness of the proposed scheme. Simulation results have verified that SST/BES has very good performances, and it cannot only avoid loads impacting the primary system, but also can prevent from voltage sags and momentary interruptions infecting the loads.